Effect of volatile boron species on the electrocatalytic activity of cathodes of solid oxide fuel cells I. (La,Sr)MnO3 based electrodes - Chen, Kongfa; Ai, Na; Zhao, L.; Jiang, San Ping (The Electrochemical Society, Inc, 2013)
The effect of volatile boron species on the microstructure and electrocatalytic activity of conventional (La,Sr)MnO3 (LSM) and nano-structured LSM infiltrated Y2O3-ZrO2 (LSM-YSZ) cathodes of solid oxide fuel cell (SOFC) is studied. The cathodes were heat-treated at 700–800°C in air for 7–30 days in the presence of borosilicate glass powder. Compared to freshly-prepared cathodes, heat-treatment in the presence of glass improves the electrocatalytic activity of LSM cathodes, but has a significant detrimental effect on the microstructure and electrochemical activity of nano-structured LSM-YSZ cathodes. Present study shows that boron is not chemically compatible with LSM and poisoning effect of boron is related to the size of LSM particles. Interaction between volatile boron species and nano-sized LSM leads to the decomposition of LSM perovskite structure and the significant degradation of the electrocatalytic activity of the electrodes. In the case of conventional LSM, the reaction between boron and LSM occurs primarily on the surface. The agglomeration of LaBO3 and formation of nonstoichiometry thin surface may be beneficial to the removal of the segregated species on the LSM surface and thus improves the performance. A reaction mechanism between volatile boron species and LSM electrodes is proposed.